PENGARUH IKLIM KERJA DAN SUPERVISI PIMPINAN TERHADAP MOTIVASI KERJA DI PANGERAN BEACH HOTEL PADANG - Musparni (Jurnal Pariwisata Bunda, 2021)
This study aimed at finding out the effect of the working climate and supervision of the leadership on the work motivation of the employees at Pangeran  Beach Hotel Padang. The research hypothesis was that work climate and leadership supervision had a significant effect on the work motivation of the employees of Pangeran  Beach Hotel Padang. The total population was 110 employees of Pangeran  Beach Hotel Padang. The sampling technique used was the Cluster Stratified Random Sampling method.  The samples were 73 employees. Data were collected through a questionnaire using a Likert scale which had been tested for its validity and reliability. As collected, the data were analyzed by Path Analysis using the SPSS (Statistical Package for Social Science) program. The findings proved that there is an influence of work climate, and supervision of leaders on the work affected the employees’ motivation at Beach Hotel Padang. To increase the work motivation of Pangeran  Beach Hotel Padang employees, employees should respond to their duties properly and also increase their sense of responsibility at work. Supervisors/leaders should increase the application of rewards and punishments. To improve the work climate, it should be encouraged to be more flexible at work, increase sympathy, provide support, and increase the courage of employees to do risky work. As employees’ motivation has already increased, they will be more diligent and serious at work.